Fusion of contrast-enhanced magnetic resonance neurography and T1-weighted imaging improves simultaneous nerve-tumor visualization in head and neck lesions - Liu, Tingting; Zhang, Zhiqing; Liu, Yuan; Su, Yu; Yu, Qun; Li, Chungao; Kong, Xiangchuang; Zhao, Jie; Huang, Shuo; Zheng, Chuansheng; Wu, Wenjun; Wang, Lixia (Frontiers in Oncology, 2025)
ObjectiveTo investigate the application value of integrating contrast-enhanced magnetic resonance neurography (CE-MRN) with contrast-enhanced T1-weighted imaging (CE-T1WI) to improve the simultaneous imaging of nerves and tumors in the head and neck.Materials and methodsA retrospective study of 31 patients (14 neurogenic, 17 non-neurogenic) with pathologically confirmed peripheral nerve tumors (2017–2024) was conducted. All underwent 3.0 T MRI, assessed by two blinded radiologists. Tumor involvement patterns, enhancement features, MRI signs, and normalized nerve signal intensity were analyzed. Diagnostic confidence and lesion conspicuity were compared across CE-MRN, CE-T1WI, and fusion images. Statistical analysis included Mann-Whitney U test and interobserver agreement (Kappa/ICC).ResultsInterobserver agreement was moderate to excellent (Kappa/ICC: 0.47-0.93). Focal involvement dominated in neurogenic tumors (92.9% vs. 52.9% diffuse in non-neurogenic, p=0.002). Traditional MRI signs: “dumbbell sign” was more frequent in neurogenic tumors (78.6% vs. 11.8%, p<0.001), while “effacement of fat plane” was common in non-neurogenic (70.6% vs. 0%, p<0.001). Novel CE-MRN signs: “enhanced target sign” (28.6% vs. 0%, p=0.032) and “nerve tail sign” (57.1% vs. 11.8%, p=0.018) were neurogenic markers, whereas “nerve effacing sign” was non-neurogenic (76.5% vs. 35.7%, p=0.033). Affected nerves showed higher signal intensity than contralateral nerves (p<0.05). Fusion images matched CE-MRN in diagnostic confidence and surpassed CE-T1WI in conspicuity (p<0.001).ConclusionImage fusion technology addressed the limitations of CE-MRN in lesion visualization, thereby enhancing diagnostic confidence. The novel signs and nerve signal alterations observed in CE-MRN provide visual evidence for the accurate diagnosis and differentiation of head and neck tumors.